The Fabrication and Mechanical Properties of Laminated ZrB2-Mo5SiB2 Ceramics with an Mo-Mo5SiB2 Interlayer - Yanfang Wang; Mingliang Li; Hailong Wang; Gang Shao; Jinpeng Zhu; Wen Liu; Hailiang Wang; Bingbing Fan; Hongliang Xu; Hongxia Lu; Rui Zhang (Metals, 2021)
The excellent physical and chemical properties of ultra-high temperature ceramics make them suitable for many high-temperature structural components, while their poor toughness and high sintering temperature become key limitations to their application. Laminated toughening has long been considered an effective toughening method to improve the mechanical properties of ceramics. In this study, laminated ZrB2-Mo5SiB2 ceramics with an Mo-Mo5SiB2 interlayer were fabricated by tape casting and hot press sintering at 1900 °C for 2 h. Different layer thickness ratios between the matrix layer and the interlayer were designed to illustrate the toughening mechanism. Both the fracture toughness and flexural strength of the laminated ceramics showed a trend of first increasing and then decreasing with the increase of the layer thickness ratio. High fracture toughness (9.89 ± 0.26 MPa·m1/2) and flexural strength (431.6 ± 15.1 MPa) were obtained when the layer thickness ratio was 13. The improvement in fracture toughness of the laminated ceramics could be attributed to the generation of the residual stress, the deflection and the bifurcation of the cracks. Residual stress that developed in the laminated ceramics was also evaluated.